A comparative evaluation of cytotoxicity of root canal sealers: an in vitro study - Gautam Pyarelal Badole; Manjusha Madhukar Warhadpande; Ganesh Kothiramji Meshram; Rakesh Namdeoraoji Bahadure; Shubha Gopal Tawani; Gopal Tawani; Shital Gautam Badole (Korean Academy of Conservative Dentistry, 2013)
Objectives The objective of this in vitro study was to evaluate and compare the cytotoxicity of four different root canal sealers i.e. Apexit Plus (Ivoclar Vivadent), Endomethasone N (Septodont), AH-26 (Dentsply) and Pulpdent Root Canal Sealer (Pulpdent), on a mouse fibroblast cell line (L929). Materials and Methods Thirty two discs for each sealer (5 mm in diameter and 2 mm in height) were fabricated in Teflon mould. The sealer extraction was made in cell culture medium (Dulbecco's Modified Eagle's Medium, DMEM) using the ratio 1.25 cm2/mL between the surface of the sealer samples and the volume of medium in a shaker incubator. Extraction of each sealer was obtained at 24 hr, 7th day, 14th day, and one month of interval. These extracts were incubated with L929 cell line and 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide (MTT) assay was done. Two-way ANOVA for interaction effects between sealer and time and Post-hoc multiple comparison using Tukey's test across all the 16 different groups were used for statistical analysis. Results Apexit Plus root canal sealer was significantly less toxic than other sealers (p < 0.05) and showed higher cellular growth than control. Endomethasone N showed mild cytotoxicity. AH-26 showed severe toxicity which became mild after one month while Pulpdent Root Canal Sealer showed severe to moderate toxicity. Conclusions Apexit Plus was relatively biocompatible sealer as compared to other three sealers which were cytotoxic at their initial stages, however, they became biocompatible with time.